Hydrogen sulfide in the pathogenesis of atherosclerosis and its therapeutic potential. Issue 1 (January 2011) - Lynn, Edward G; Austin, Richard C
Hydrogen sulfide (H2 S) was the third gaseous transmitter to be discovered, along with nitric oxide and carbon monoxide, and has been proposed to be involved in numerous physiological processes and pathology of various diseases. Hyperhomocysteinemia is an independent risk factor for cardiovascular disease, including atherosclerosis. Atherosclerosis is characterized by multiple key events including endothelial dysfunction, monocyte infiltration and their differentiation into macrophages, conversion of lesion-resident macrophages into foam cells, and smooth muscle cell proliferation. Increasing evidence has indicated that H2 S plays a potentially significant role in all of these biological processes and that malfunction of H2 S homeostasis may contribute to the pathogenesis of atherosclerosis. Experiments have demonstrated that H2 S supplementation ameliorated many of these atherogenic processes and hence, such supplementation potentially may prove to be of therapeutic benefit in the prevention or treatment of atherosclerosis. H2 S levels may be induced by the administration of H2 S or H2 S donors, or alternatively be reduced by the administration of specific cystathionine β-synthase or cystathionine γ-lyase inhibitors. However, issues remain with the potential use of currently available H2 S-modulating agents in a clinical setting. This review will provide a description of the current literature on the involvement of H2 S in these key aspects of vascular biology that contribute to the development of atherosclerosis, as well as the therapeutic potential of currently available H2 S-modulating agents.